2020
DOI: 10.1093/cid/ciaa325
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Clinical and Pathological Manifestations of Coronavirus Disease 2019 (COVID-19) in a Golden Syrian Hamster Model: Implications for Disease Pathogenesis and Transmissibility

Abstract: Background A physiological small animal model that resembles COVID-19 with low mortality is lacking. Methods Molecular docking on the binding between angiotensin-converting enzyme 2 (ACE2) of common laboratory mammals and the receptor-binding domain of the surface spike protein of SARS-CoV-2 suggested that the golden Syrian hamster is an option. Virus challenge, contact transmission, and passive immunoprophylaxis were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

141
1,362
6
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,026 publications
(1,562 citation statements)
references
References 27 publications
141
1,362
6
16
Order By: Relevance
“…This allowed the authors to predict that hamsters could be infected, which was experimentally confirmed -underlining the reliability of in silico modeling-and could be subsequently at the origin of inter-animal transmission. However, hamsters, although developing clinical signs of the infection and relative histopathological changes, did not die 50 : we speculate that lethality may be related to Spike/ACE2 affinity. On the other hand, the lower affinity in bat could explain -besides a better immune control-why these animals are carriers without dying.…”
Section: Discussionmentioning
confidence: 74%
“…This allowed the authors to predict that hamsters could be infected, which was experimentally confirmed -underlining the reliability of in silico modeling-and could be subsequently at the origin of inter-animal transmission. However, hamsters, although developing clinical signs of the infection and relative histopathological changes, did not die 50 : we speculate that lethality may be related to Spike/ACE2 affinity. On the other hand, the lower affinity in bat could explain -besides a better immune control-why these animals are carriers without dying.…”
Section: Discussionmentioning
confidence: 74%
“…Non-human primate models have proven to be highly valuable for other infectious diseases, but are expensive to maintain and numbers of experimental animals are limited. Our results provide an extended list of potential species that might be useful as animal models for SARS-CoV-2 infection and pathogenesis, including Chinese hamster and Syrian/Golden hamster (49) , and large animals maintained for biomedical and agricultural research (e.g., domesticated…”
Section: Discussionmentioning
confidence: 99%
“…Data on susceptibility of wild animals to SARS-CoV-2 is still very limited. It has been reported that a captive Malayan tiger was infected by SARS-CoV-2(9) and that domestic cats, ferrets(47) , rhesus macaques(48) and Syrian golden hamsters(49) are susceptible to experimental infection by SARS-CoV-2. These results agree with our predictions of ACE2 binding ability to SARS-CoV-2 S(Fig.…”
mentioning
confidence: 99%
“…Since December of 2019, scientists all over the world have been working to establish animal model of COVID-19. So far there are several models reported in preprinted journals or peer-reviewed published journals, including two small murine models (hACE2 transgenic mouse 14 and Gold Syrian hamster 15 ), one ferret model 16 Retrospective studies of clinical features of COVID-19 show that older patients have more severe diseases, which may be associated with comorbidities, including tumor, diabetes, obesity, hypertension, heart diseases and so on [18][19][20] . These underlying diseases may make senior patients more susceptible to SARS-CoV-2 infection and worsen COVID-19.…”
Section: Sars-cov-2 Recently Reported As Another Novel Coronavirus Ementioning
confidence: 99%